'L'enclume toujours chaude': Émile Zola's Newspaper Trilogy. (2nd October 2017) - White, Nicholas
ABSTRACT: Recent research on Émile Zola's involvement with the French press of the late Second Empire and early Third Republic has clarified the shape of this history of his engagement with journalism, including a supposed absence from the fray between 1881 and 1895. This article, however, identifies in the period 1888 to 1892, between the idealism of Le Rêve and the reflexivity of Le Docteur Pascal, a period of particular reflection on the press by Zola which illuminates 'le retour du réel et de l'actualité' in his novels: La Bête humaine, L'Argent and La Débâcle .